Continuous forearm cooling attenuates gastrointestinal temperature increase during cycling - Hedge, E. T.; Zuj, K. A.; Stothart, A. G.; Gavel, E. H.; Goodman, L. S.; Buckrell, A. J. M.; Peterson, S. D. (Journal of Sports Sciences, 2021)
Hot environmental conditions can challenge thermoregulation resulting in exacerbated heat strain. This study evaluated the influence of continuous inner forearm cooling on gastrointestinal temperature (TGI) and physiological responses to exercise in hot (30°C) and humid (relative humidity: 70%) conditions. Eleven trained cyclists (seven male age: 37±12 years; four female age: 41±15 years; mean±standard deviation) performed two experimental trials, cycling at 66% of their self-reported functional threshold power (average work rate over an hour of maximum effort cycling; 175±34W) for 45 minutes in an environmental chamber. One trial employed continuous inner forearm cooling (COOL) with 5°C water passing through aluminum heat exchangers, while the other had no cooling (CONTROL). Heat was removed from the body at an average rate of 30.3±6.6W during the COOL trial resulting in an attenuation of TGI rise (CONTROL: 2.46±0.70, COOL: 2.03±0.63°C·h-1; p=0.002). The change in heart rate from the 10th minute to the end of exercise, as an indicator of cardiovascular drift, was reduced (CONTROL: 20±7, COOL: 17±6beats/min; p=0.050) and end-exercise thermal comfort was improved in the COOL trial with a trend for reduced rating of perceived exertion (p=0.055). Findings suggest that continuous cooling of the inner forearms can attenuate the rise of TGI and help mitigate the risk of heat injury during exercise in hot and humid conditions.